Erythema migrans-like lesions associated with Borrelia afzelii infection in a European badger, Meles meles - Mihalca, Andrei Daniel; Deak, Georgiana; Cazan, Cristina Daniela; Mechouk, Noureddine; Negoescu, Andrada; Taulescu, Marian; Gherman, Călin Mircea (Frontiers in Veterinary Science, 2025)
IntroductionErythema migrans (EM), a characteristic skin lesion, is a well-known clinical outcome of Lyme borreliosis in humans, caused by various Borrelia burgdorferi sensu lato (s.l.) species. However, its occurrence in animals, mainly wildlife, has been largely unexplored. This report presents a possible case of EM in a European badger (Meles meles) from Romania.Materials and methodsThe badger exhibited multiple erythematous lesions on its ventral body surface, and these lesions were heavily infested with Ixodes ricinus ticks. Histological examination of skin biopsies was conducted to assess inflammatory reactions. Molecular analysis was performed to detect Borrelia DNA in the lesions.ResultsHistological examination revealed a mild, chronic inflammatory reaction consistent with EM-like lesions as observed in humans. Molecular analysis confirmed the presence of Borrelia afzelii DNA in the skin lesions.ConclusionThese findings underscore the importance of wildlife surveillance in understanding the ecoepidemiology and pathogenesis of Lyme borreliosis. Badgers, as potential reservoir hosts, may play a role in the disease cycle.